Keefektifan Variasi Dosis Tawas dalam Menurunkan Kandungan COD (Chemical Oxygen Demand) Limbah Cair Industri Penyamakan Kulit Magetan - Pradina, Pristian; , Dwi Astuti, SKM., M.Kes; , Sri Darnoto. SKM. MPH (2015)
The high content of COD (Chemical Oxygen Demand) in the waste water industry affects the quality of water which adversely affects the health of the organism. COD levels based on the results of preliminary tests conducted at the IPAL LIK Tannery Magetan is 117.4 mg / l. The results exceeded the quality standard of waste water is allowed. One way that can be done to reduce levels of COD is the process of coagulation using coagulant alum. The purpose of this study to determine the effectiveness of alum dose variation to the reduction of waste water COD levels.Processing using a variation of alum dose of 0.25 g / l, 0.5 g / l and 0.75 g / l with a quick manual method stirring of 100 rpm for two minutes. The average yield decreased levels of COD per dose variation of 30.4 mg / l; 28.03 mg / l; and 16.53 mg / l. Dose effective to lower COD levels is 0,5 gr/l with a presentage of 23,20 %l. Suggested for further research to be tested using the coagulant doe variation other than alum. So as to determine the level of the type and dose variation coagulant.